2007
DOI: 10.1177/1527002508316266
|View full text |Cite
|
Sign up to set email alerts
|

Fan Substitution and the 2004-05 NHL Lockout

Abstract: This study estimates fan substitution in sports using the 2004-05 National Hockey League (NHL) season-long lockout as a natural experiment. The authors find that NHL fans substitute minor league and junior league hockey for the NHL. Because this is not due to a change in the price of a substitute good, the findings point to pure substitution effects without income effects. The findings have implications for future work on fan demand, especially for those studying habit and loyalty, or sports policy. I n this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
27
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 8 publications
5
27
1
Order By: Relevance
“…While the positive effect of team quality and age are well-established and straightforward in their interpretation, others demand more consideration. The notion of sporting contests as substitutes or complements for one another is an important topic among sport management researchers (e.g., Allan & Roy, 2008;Baimbridge, Cameron, & Dawson, 1996;Garcia & Rodriguez, 2002;Siegfried & Hinshaw, 1979;Winfree & Fort, 2008;Winfree, McCluskey, Mittelhammer, & Fort, 2004), often by way of broadcast as a potential substitute or complement for live spectatorship. Although our data did not support a substitution effect related to an active local team in the MLB playoffs, the broadcast of another NFL game was indeed a viable substitute for an out-of-market game.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the positive effect of team quality and age are well-established and straightforward in their interpretation, others demand more consideration. The notion of sporting contests as substitutes or complements for one another is an important topic among sport management researchers (e.g., Allan & Roy, 2008;Baimbridge, Cameron, & Dawson, 1996;Garcia & Rodriguez, 2002;Siegfried & Hinshaw, 1979;Winfree & Fort, 2008;Winfree, McCluskey, Mittelhammer, & Fort, 2004), often by way of broadcast as a potential substitute or complement for live spectatorship. Although our data did not support a substitution effect related to an active local team in the MLB playoffs, the broadcast of another NFL game was indeed a viable substitute for an out-of-market game.…”
Section: Discussionmentioning
confidence: 99%
“…Although flow theory typically relates only to adjacent programming on the same network, in the case of NFL programming it is worthwhile to investigate whether a cross-channel effect exists as the foundational tenets of flow theory, namely audience availability and viewer program preference, are applicable regardless of channel. Given the habitual nature of sports viewership well-documented in the sport management literature (e.g., Borland & Lye, 1992;Owen & Weatherspoon, 2004;Spenner, Fenn, & Crooker, 2010;Winfree & Fort, 2008;Won & Lee, 2008) coupled with the fact that Sunday afternoon games always appear on one of two networks, we assume fans have some awareness of the channels on which games may appear.…”
mentioning
confidence: 99%
“…To that extent, a substitute for a minor league game could include any other local entertainment establishment such as movie theaters, public swimming pools, or the local bowling alley. Moreover, there is a mounting evidence that sports fans who attend minor league games also substitute major league games and vice versa (Winfree and Fort, ). When looking specifically at ticket price, Gitter and Rhoads () show that a minor league team will experience an increase in attendance if an MLB team within 100 mi increases its ticket price.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Leadley and Zygmont, 2006;and Winfree and Fort, 2008, report on factors impacting hockey. In their study, Paul and Weinbach (2011) found that "Fan demand for Canadian Hockey junior league level of hockey is found to be sensitive to the success of the home team and to exhibit normal consumer responses to weekday and monthly effects with weekends being more popular and attendance increasing throughout the season toward the playoffs.…”
Section: Basketballmentioning
confidence: 99%